THE EFFECT OF PEER FEEDBACK ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT AT MAS PP AT-TAUFIQURRAHMAN - Dewi, Hotna (BRIGHT VISION Journal of Language and Education, 2022)
This  study  found  that  peer  feedback  effect  on  students’  achievement  in  writing narrative text. It was conducted by using experimental design. The population was X-1 and X-2 students of Mas Pp At-taufiqurrahman. There are consist 40 students. The sample of two classes devided into two groups, experimental group and control group which were chosen random sampling by using lottery technique. The grade X-1 as experimental group was taught by using peer feedback   and grade X-2 as control group was taught conventional method. The instruments used in this research was written test.  After analyzing the data, the writer got; The students achievement in writing narrative text by peer feedback got the mean 77.700 and standar deviation was 8.985 ; The students’ achievement in writing narrative text by using conventional  got the mean 56.600 and standard deviation was 6.269. The value of t- observed was 3.207 and that of t-table was 1.671. So the value of t-observed was higher than that of t-table. It showed that Ho rejected and Ha accepted. there was significant effect of using peer feedback strategy on students’ achievement in writing narrative text.